PERAN BADAN KOORDINASI KEGIATAN KESEJAHTERAAN SOSIAL KALIMANTAN BARAT TERKAIT REHABILITASI NARKOBA - Anny Riwayati; Sri Winarsih; Siti Izatul Zahra; Syarifah Ema Rahmaniah; Herlan (Halu Oleo University, 2024)
The purpose of this study was to determine the role of the West Kalimantan Social Welfare Coordinating Board in relation to drug rehabilitation. This study uses a qualitative method that aims to obtain a clear picture of a problem, which will be focused on collecting data or information on the object. The results of the study indicate that the drug rehabilitation places provided by the Government in West Kalimantan are still lacking. The results of the study stated that there are many cases in the community, of drug users who do not receive rehabilitation. BK3S has not played a role in drug rehabilitation but has carried out preventive education in the form of socialization to the community in preventing drugs. In the future, BK3S hopes to be able to carry out drug rehabilitation and have a sufficient budget to do so because drug rehabilitation requires a large budget.